Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1537-2995.2008.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion efficacy of ABO major‐mismatched platelets (PLTs) in children is inferior to that of ABO‐identical PLTs

Abstract: These data clearly indicate that in children ABO major-mismatched PLT transfusions result in inferior transfusion efficacy, with the only exception of group A(2) PLTs. ABO minor-mismatched PLTs showed comparable efficacy to identical transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
(92 reference statements)
0
43
2
Order By: Relevance
“…In another prospective study, the authors analyzed the post-transfusion PLT increments after 400 PLT transfusions in 50 pediatric patients with a variety of hematology-oncology malignancies. ABO-major mismatched PLT transfusions resulted in lower post-transfusion PLT increments compared to ABO identical PLT transfusions (p = 0.034) [45]. However, none of these studies reported any clinical outcomes in the recipients of matched or mismatched PLTs.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitymentioning
confidence: 99%
“…In another prospective study, the authors analyzed the post-transfusion PLT increments after 400 PLT transfusions in 50 pediatric patients with a variety of hematology-oncology malignancies. ABO-major mismatched PLT transfusions resulted in lower post-transfusion PLT increments compared to ABO identical PLT transfusions (p = 0.034) [45]. However, none of these studies reported any clinical outcomes in the recipients of matched or mismatched PLTs.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitymentioning
confidence: 99%
“…In the present study, the prospectively registered transfusion efficacy of APCs was analyzed retrospectively by reviewing the records of all patients having received at least one APC between January 2004 and December 2010 at the Division of Pediatric Hematology and Oncology, Department of Pediatrics, University of Bern, Switzerland. This data set included the data of our two former prospective trials evaluating the effects of high-yield thrombocytapheresis on the quality of APCs [16] and the influence of ABO blood group matching between PLT donor and recipient on post-transfusion PLT increment [17]. In addition to the 1-hour percent PLT recovery (PPR 1h ), side effects of PLT transfusions and data on the production process of APCs were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…With a random intercept per patient, LME accounts for the correlation among multiple transfusions given to the same patient. For multivariate analysis, storage time, applied apheresis procedure, apheresis yield, ABO transfusion constellation, body weight of recipients, and PLT count before transfusion were used as covariates [16,17]. Two-sided tests were used throughout, and p values < 0.050 were considered significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An impact of ABO mismatching on transfusion efficacy in terms of lower platelet count increments has been described [14,15,23]. Yet, only a few studies have focused in endpoints such as patient survival or bleeding rates.…”
Section: Discussionmentioning
confidence: 99%